Pengaruh Pengelolaan Arus Kas Operasional terhadap Profitabilitas pada PT. Prima Unggul Global - Denil Heriawan; Abd. Hafid; Hartas Hasbi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the effect of operating cash flow management on the profitability of PT. Prima Unggul Global, a company engaged in Hajj and Umrah travel services, characterized by seasonal operations and vulnerability to regulatory changes and exchange rate fluctuations. The research adopts a quantitative associative approach using secondary data derived from the company’s financial statements for the period 2022–2024. Operating cash flow serves as the independent variable, while profitability is measured using the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) as dependent variables. Data analysis was conducted through simple linear regression using the SPSS application. The results indicate that operating cash flow management has a significant effect on the company’s Net Profit Margin (NPM), with a regression coefficient of 0.000000008228 and a significance level of 0.00 (<0.05). It also significantly affects Return on Assets (ROA), with a coefficient of 0.000000001308 and a significance level of 0.00 (<0.05). Similarly, it has a significant impact on Return on Equity (ROE), with a coefficient of 0.000000001882 and a significance level of 0.01 (<0.05). These findings demonstrate that operating cash flow management significantly influences the profitability of PT. Prima Unggul Global.